PENGEMBANGAN MANAJEMEN MUTU SEKOLAH - Mada Sutapa (Fakultas Ilmu Pendidikan UNY, 2009)
Management paradigms in the total quality of school education quality in the instiiutional development of schools. which include the ability to make the organization of schools (school renewal). Updates to the school (School Reform) and the process need not be run automatically. It is necessary for a positive attitude' (positive thinking) on the renewal 0/ all the components in the school and the use of resources needed to make changes. Changes in the dimensions 0/ school quality management does not only include school management, but is expected to create a climate conducive to personal development of students. not just a mechanical and bureaucratic institltfiOlls,but a school (education) of innovative and democratic. Keywords: Total Quality in Education. Quality Management School.